Penyelenggaraan Pembangunan NKRI Menuju Negara Maritim Berdasarkan Prinsip Negara Kepulauan - Putra, Aryono; Arafat, Yasser (Universitas Borneo Tarakan, 2018)
ABSTRACT?Indonesia has been deprived of its own true roots as a maritime country. This is the success of the colonial Dutch colonialists who do